Indications for absorbable steroid‐eluting sinus implants: Viewpoint via the Delphi method. Issue 10 (5th July 2022) - Lee, Victoria S.; Patel, Prayag; O'Brien, Daniel; Scangas, George A.; Campbell, Raewyn G.; Chandra, Rakesh; Davis, Greg E.; Han, Joseph K; Le, Christopher H.; Lee, Jivianne; Luong, Amber U.; Poetker, David M.; et al.
Abstract: Absorbable steroid‐eluting sinus implants provide targeted corticosteroid release over a sustained period and are designed to prevent both undesirable adhesion formation and sinus ostia restenosis. Here, we highlight the key evidence of these implants to date and query a group of experts via a Delphi process on the indications and optimal timing for intraoperative or in‐office placement of these implants. Six of a total of 12 statements reached consensus and were accepted. Overall, experts largely agree that intraoperative or in‐office use of steroid‐eluting stents could be considered for patients: (1) who are diabetic or intolerant of oral steroids, (2) undergoing extended frontal sinus surgery, and (3) with recurrent stenosis. Given the lack of expert consensus on other key statements, clinicians should carefully consider these treatment options on a case‐by‐case basis after shared decision‐making.